2022
DOI: 10.3390/ijms232314917
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stemness/Epithelial–Mesenchymal Transition Axis Influences Metastasis and Castration Resistance in Prostate Cancer: Potential Therapeutic Target

Abstract: Prostate cancer (PCa) is a leading cause of cancer death in men, worldwide. Mortality is highly related to metastasis and hormone resistance, but the molecular underlying mechanisms are poorly understood. We have studied the presence and role of cancer stem cells (CSCs) and the Epithelial–Mesenchymal transition (EMT) in PCa, using both in vitro and in vivo models, thereby providing evidence that the stemness–mesenchymal axis seems to be a critical process related to relapse, metastasis and resistance. These ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…The aberrant m6A peaks representing mRNAs were enriched in hallmarks such as early estrogen response, EMT, TNFa signaling via NF-κB and angiogenesis, which are related to cancer metastasis ( Fig. 2B ) [ [13] , [14] , [15] ]. In addition, the 3164 hypermethylated m6A modification peaks representing mRNAs in the metastasis group were found to be enriched in KEGG pathway terms such as ECM-receptor interaction, protein digestion and absorption, cell adhesion molecules and proteoglycans in cancer ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aberrant m6A peaks representing mRNAs were enriched in hallmarks such as early estrogen response, EMT, TNFa signaling via NF-κB and angiogenesis, which are related to cancer metastasis ( Fig. 2B ) [ [13] , [14] , [15] ]. In addition, the 3164 hypermethylated m6A modification peaks representing mRNAs in the metastasis group were found to be enriched in KEGG pathway terms such as ECM-receptor interaction, protein digestion and absorption, cell adhesion molecules and proteoglycans in cancer ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, CL2 showed downregulation of the genes involved in drug metabolism and cellular response while upregulation of the genes associated with drug resistance. In cancer cells, the acquisition of stemness-like as well as cell dedifferentiation (mesenchymal) traits can facilitate the formation of metastases and lead to the development of drug resistance 76 . Further analysis of the metastatic potential of CL2 indicated that the cluster is enriched with genes associated with vasculature and angiogenesis.…”
Section: Scellbow Enables Pseudo-grading Of Metastatic Prostate Cance...mentioning
confidence: 99%
“…Metastatic contributors have been identified too, and they include the loss of PTEN, aberrations in the PI3K-AKT signaling pathway, and the acquisition of DNA repair defects [ 18 ]. The degree of stemness observed in a cancer is also known to influence CR and metastasis [ 19 , 20 , 21 ]. Cancer stem cells (CSC) are thought to compose only about 1% of a tumor’s mass, though they are crucial in the tumor’s growth and proliferation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this process, malignant epithelial cells gain mesenchymal-like traits and become highly invasive in doing so [ 24 ]. The formation of CSCs through the process of EMT provides a tumor with a high capacity for colonization, ultimately promoting the cancer’s metastasis [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%